Applying the jigsaw technique to improve reading comprehension skill with students of 4th year of basic education at Luis Humberto Benitez Costa school academic period 2013-2014 - Pineda Castillo, Andrea Gisela (2015)
The purpose of this action research was to investigate the use of the jigsaw technique in the improvement of reading comprehension skill with fourth year of basic education at “Luis Humberto Benitez Costa” school. An intervention plan with twelve sessions was carried out to improve the reading comprehension skill. One researcher-made test was designed and used to measure the ten students’ progress and advantages of jigsaw use. Additional instruments like field diary and checklists were also used regularly to appreciate the students’ growth. The results indicated that the use of the Jigsaw technique facilitated meaningfully the improvement of reading comprehension which was reflected in the noticeable increase of the posttest scores and students’ progress during the intervention. It would be fair to conclude that this study helped the students to improve their reading comprehension level, the researcher sharpen her teaching skills and the community will have well-prepared candidate teachers.